Research Anthology on Preparing School Administrators to Lead Quality Education Programs 2021
DOI: 10.4018/978-1-7998-3438-0.ch017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Higher Education Institutions through Agency and Resource-Capabilities Theories

Abstract: The objective of this chapter is to explain through the agency theory and theory of resources and capacities as is the process of assessment in higher education institutions. A model is presented to measure the perception of service quality by students of the Technological Institute of Celaya, as part of the system of quality control, based on the theoretical support of several authors who have developed this topic (SERVQUAL and SERPERF) an instrument adapted to the student area of the institution called SERQU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Khan et al (2021) also concluded that the concept of satisfaction remains very imperative for practitioners and academic researchers in the educational sector. A Series of attempts have been made by scholars (Hopkins, 2021;Smart, 2021) to quantify and expound institutional satisfaction, yet there appears to be less harmony (Vargas-Hernández et al, 2021) regarding its designation from the educational perspective. It is seen as a post-purchase behavior (Marques et al, 2021) for evaluating an individual judgment concerning a specific service.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Khan et al (2021) also concluded that the concept of satisfaction remains very imperative for practitioners and academic researchers in the educational sector. A Series of attempts have been made by scholars (Hopkins, 2021;Smart, 2021) to quantify and expound institutional satisfaction, yet there appears to be less harmony (Vargas-Hernández et al, 2021) regarding its designation from the educational perspective. It is seen as a post-purchase behavior (Marques et al, 2021) for evaluating an individual judgment concerning a specific service.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%